1986
DOI: 10.1111/j.1365-2990.1986.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrastructural Analysis of the Effects of Accumulation of Neurofibrillary Tangle in Pyramidal Neurons of the Cerebral Cortex in Alzheimer's Disease

Abstract: Quantitative morphometric (stereological) methods have been used to assess the effects of accumulation of neurofibrillary material on the fine structure of pyramidal cells in biopsy specimens of temporal cortex from nine patients with Alzheimer's disease. When compared with non-tangled cells from the same patients, tangled cells show an increase in total area of cytoplasm due to the accumulation of tangle and a reduction in the area of the nucleus; the area proportion of the cell body occupied by total cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
1

Year Published

1988
1988
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 15 publications
3
19
1
Order By: Relevance
“…This suggests that either P301L tau induces a different pathological mechanism than overexpressed WT tau or that tau action on mitochondria transport in cell culture cannot be extrapolated over to the mouse model. Consistent with our findings, similar numbers of mitochondria were reported in NFT-bearing and non-NFT-bearing cells in AD (52). Alternatively, tau accumulation could have direct repercussions on the mitochondria because the accumulation of increasingly insoluble ATP synthase ␣-chain together with NFTs has been shown in AD brains, whereas detergent soluble levels were reduced (53).…”
Section: Discussionsupporting
confidence: 91%
“…This suggests that either P301L tau induces a different pathological mechanism than overexpressed WT tau or that tau action on mitochondria transport in cell culture cannot be extrapolated over to the mouse model. Consistent with our findings, similar numbers of mitochondria were reported in NFT-bearing and non-NFT-bearing cells in AD (52). Alternatively, tau accumulation could have direct repercussions on the mitochondria because the accumulation of increasingly insoluble ATP synthase ␣-chain together with NFTs has been shown in AD brains, whereas detergent soluble levels were reduced (53).…”
Section: Discussionsupporting
confidence: 91%
“…How ever, in our sample of AD patients, NFT-bearing neurons contain significantly less lipofuscin than either adjacent non-NFT-bearing neurons or neurons of age-matched controls in regions CA2 and CA3 of the hippocampus. Our results are in contrast with the findings of Mann et al [13] who reported no changes in lipofuscin accumulation in NFT-bearing neurons, and with those of Sumptner et al [14] who noted an increase in lipofuscin content in neurons of AD brains. These disparities may be due to regional differences, or to the techniques employed to quantify the lipopigment.…”
Section: Discussioncontrasting
confidence: 57%
“…The critical role of inhibition of ␣-KGDH by H 2 O 2 revealed in this study could be important in the pathogenesis of late-onset neurodegenerative diseases such as Parkinson's disease (Mizuno et al, 1994) and Alzheimer's disease (Blass and Gibson, 1991;Gibson et al, 1998a), during which the activity of ␣-KGDH was found to be inhibited (for review, see Gibson et al, 2000). The sensitivity of ␣-KGDH in nerve terminals could be particularly relevant to the suggestion that nerve terminals are the primary site of mitochondrial damage in Alzheimer's neurons (Sumpter et al, 1986;Blass and Gibson, 1991).…”
mentioning
confidence: 99%
“…Studying oxidative stress-induced loss of functions in in situ mitochondria in nerve terminals is relevant in the light of the observation that over the progress of certain neurodegenerative diseases, such as Alzheimer's disease, mitochondrial damage appears to start at nerve terminals (Sumpter et al, 1986; see also Blass and Gibson, 1991). In this preparation a limited capacity of the respiratory chain in the early stage of an H 2 O 2 -induced oxidative stress appeared to be satisfactory under resting conditions, but when combined with other insults (mitochondrial blockers, [Na ϩ ] i load) it resulted in a complete functional collapse (Chinopoulos et al, 2000).…”
mentioning
confidence: 99%